1999
DOI: 10.1366/0003702991945560
|View full text |Cite
|
Sign up to set email alerts
|

Raman Performance Characteristics of Teflon®-AF 2400 Liquid-Core Optical-Fiber Sample Cells

Abstract: Several properties of Teflon®-AF liquid-core optical-fiber (LCOF) sample cells relevant to their utility in analytical Raman spectroscopy have been investigated. These include the nature and extent of cladding-related background and its effect on signal-to-noise ratio, and the dependence of intensity enhancement on LCOF length, core diameter, excitation wavelength, and scattering wavelength. Significant improvements in signal-to-noise ratio relative to conventional sampling techniques were demonstrated in LCOF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 42 publications
0
38
0
2
Order By: Relevance
“…LCOFs greatly enhance the number of scattered photons that can be collected over a given integration time, with the additional advantage of requiring a small sample volume in the order of 1 µL [23]. Building on the work of Altkorn et al [24,25], the experiments of Qi and Berger [19,23,26,27] demonstrated the application of LCOFs for multicomponent analysis. An illustration of the LCOF Raman system used by Qi and Berger in 2007 [27] for quantifying different analytes in blood serum and urine samples is given in Fig.…”
Section: A Optical Systems For Multicomponent Analysis With Raman Spmentioning
confidence: 99%
“…LCOFs greatly enhance the number of scattered photons that can be collected over a given integration time, with the additional advantage of requiring a small sample volume in the order of 1 µL [23]. Building on the work of Altkorn et al [24,25], the experiments of Qi and Berger [19,23,26,27] demonstrated the application of LCOFs for multicomponent analysis. An illustration of the LCOF Raman system used by Qi and Berger in 2007 [27] for quantifying different analytes in blood serum and urine samples is given in Fig.…”
Section: A Optical Systems For Multicomponent Analysis With Raman Spmentioning
confidence: 99%
“…μg/ml level,~10 À8 M Micro-channel with AF 2400 SERS, micro-fluid [117] Urea~0.15 M Micro-channel with PDMS Microfluidic chip, Forward scattering [108] Methanol ND Teflon @ AF-2400 capillary tube Forward scattering [69] Trans-stilbene~0.25 M Quartz capillary tube Back-scattering [72] R6G~10 À9 M Hollow-core silica optical fibre SERS, Back-scattering [56] Adenosine 5 0 -monophosphate, Guanosine 5 0 -monophosphate, Uridine 5 0 -monophosphate 0.1 mg/ml, 0.1 mg/ml, 0.1 mg/ml Teflon @ AF-2400 Forward scattering [105] Methanol, ethanol, acetonitrile ND Teflon @ AF-2400 capillary tubing Forward scattering [118] 4-Nitroaniline, 4-nitrophenol, 2,4-dinitrophenol, nitrobenzene 10 μg/ml, 50 μg/ml, 250 μg/ml, 500 μg/ml, Teflon AF2400 capillary tube Forward scattering, Liquid chromatography [119] Ethanol water, KNO 3 0.022 ± 0.005%, 0.08 g/l Optofluidic jet waveguide Orthogonal excitation approach, fibre excitation/collection approach [120] Aqueous ethanol ND Teflon AF2400 waveguide Back-scattering [74] Biochemical creatinine dissolved in water and in urine mg/dl level Teflon @ -AF LCOFs geometry Back-scattering [121] β-carotene 2.5 × 10 À10 M Teflon AF2400 waveguide Back-scattering [122] Lysozyme~54 μM Teflon-AF capillary Back-scattering [10] Aqueous phenylalanine~6 × 10 À4 M T e f l o n @ AF-2400 capillary tubing Back-scattering [123] Mefloquine, Chloroquine 0.08 μM, 0.008 μM Teflon-AF capillary Back-scattering, UV Resonance Raman scatterers [33] 2-Propanol 5% Teflon AF2400 tube with a L-joint outlet 90°scattering [124] Carbon disulphide (CS2) influenced by β-carotene~1 0 À12 mol/l Hollow-core silica optical fibre Forward scattering, SRS [125,126] Carbon disulphide ND Multimode hollow-core optical fibre Stimulated Rayleigh-Kerr and Raman-Kerr scattering, Forward scattering [127] I 2 in benzene mg/l level Hollow-core quartz optical fibre Resonance Raman scatterers [128] Carbon disulphide ND Quartz-glass hollow fibre Stimulated Kerr scattering, Forward scattering [129] β-carotene molecule 10 À16 M Long-pathlength quartz glass tube Resonance Raman scattering, back-face collection geometry [130] 1,4-Bis(4-vinylpyridyl) phenylene (BVPP) 1 × 10 À8 mol/l U-shape microtube Back-scattering, SERS 1-Naphthalenethiol 10 μM HCPCFs MFC, BS, SF [66] Ethanol ND HCPCFs NSF, FS…”
Section: Microstructured Photonic Crystal Fibre Probementioning
confidence: 99%
“…To characterize scattering losses that were due to the LCOF walls, we used an approach based on earlier work by Altkorn et al 5,6,13 in which an optical fiber source within the LCOF is translated. 8 Briefly, an optical fiber ͑i.d., 100 m; o.d., 120 m; NA, 0.2; Thorlabs, Inc.) was inserted into one end of the LCOF, which was filled with deionized water.…”
Section: B Determination Of Lcof Scattering Lossmentioning
confidence: 99%
“…LCOF Raman sensitivity enhancements over traditional geometries (square cuvette, rounded vial) as high as 500 have been reported for aqueous specimens at various wavelengths. [3][4][5][6][7][8] Measurements of biomedical samples such as urine and aqueous protein solution were also recently explored. 8 -10 The LCOF enhancement introduces a complication: The enhancement depends on the absorption spectrum of the sample.…”
Section: Introductionmentioning
confidence: 99%